New records of hypopigmentation in two captive squirrel monkeys (Saimiri spp.) in Brazil and Colombia - Silva e Silva, Roginey; O. Montilla, Sebastián; da Silva, Claudia Regina; Hilário, Renato Richard (Therya Notes, 2026)
Despite the increasing frequency of reports of primates with anomalous pigmentation in scientific literature, there is still a lack of knowledge about these disorders in many primate species. Here, we report two cases of hypopigmentation in squirrel monkeys (genus Saimiri) in Brazil and Colombia. We describe two cases of hypopigmentation in individuals that came to our attention opportunistically. The first individual had leucistic characteristics (completely depigmented pelage, but normally colored eyes) and was observed in Macapá, in the Brazilian Amazon. The other individual showed characteristics of albinism (depigmented pelage and eyes) and was recorded in Armenia, central Colombia. Neither individual showed agonism towards humans, likely being captive primates, which may have favored their survival into adulthood. Our records are the first with images and exact coordinates for species of the genus Saimiri. The relative lack of knowledge about hypopigmentation in animals highlights the need for more research focused on them. In this context, given that most primate species are diurnal and relatively easy to observe, studies on primates may help elucidate ecological aspects related to the fitness of hypopigmented individuals. Moreover, there appears to be a growing number of reports of primates from different species with these disorders, and our reports may contribute to increase the knowledge about hypopigmentation in wild animals.